Rezension von: Weidmann, Jens; Gebert, Andreas, Die Gewässergüte der Murr 1984 - Merz, Wolfgang (Backnanger Jahrbuch, 1994)
Jens Weidmann und Andreas Gebert: Die Gewässergüte der Murr 1984. Remshalden-Buoch: Natur-Rems-Murr-Verlag 1986. 28 S. (= Natur an Rems und Murr 4)